2023
DOI: 10.1063/5.0137792
|View full text |Cite
|
Sign up to set email alerts
|

Accurate storm surge prediction using a multi-recurrent neural network structure

Abstract: This paper considers storm surge prediction using a neural network and considering multiple physical characteristics. Based on the factors that influence storm surges and historical observation data, we divide the input to the neural network into time features extracted from the prediction target and the auxiliary features that affect storm surges, and construct a feature gate within multiple recurrent neural network (RNN) cells. Historical hurricane data are used to assess the effectiveness and accuracy of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…In terms of timeliness, an operational forecast usually can give a longer forecast horizon of over 72 h. However, the forecast horizons of ML models are usually up to 12 h ahead [10,49,102,139,149]. Only a small part of studies extended the lead time to 24 h [44,83], and fewer studies attempted to output the forecast water level time series with a length of over 24 h [38,48,62,78,79].…”
Section: When Does ML Perform Better Than Traditional Methods?mentioning
confidence: 99%
See 3 more Smart Citations
“…In terms of timeliness, an operational forecast usually can give a longer forecast horizon of over 72 h. However, the forecast horizons of ML models are usually up to 12 h ahead [10,49,102,139,149]. Only a small part of studies extended the lead time to 24 h [44,83], and fewer studies attempted to output the forecast water level time series with a length of over 24 h [38,48,62,78,79].…”
Section: When Does ML Perform Better Than Traditional Methods?mentioning
confidence: 99%
“…For example, Bai and Xu [49] found that for two different types of hurricanes, different combinations of predictors could give the best prediction. By comparing different characteristic inputs, Feng and Xu [102] demonstrated that wind speed was the most important physical factor before the storm surge peaked, while pressure became the dominant feature influencing surge heights afterward. Rus et al [79] performed an ablation study to evaluate the importance of individual feature encoders, indicating that the removal of the atmospheric encoder gave rise to the most significant performance decline.…”
Section: Feature Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Machine learning has been applied in climate prediction [2], and many scholars have used machine learning to conduct research and find applications in the field of storm surges. Lei [3] used the recurrent neural network (RNN) to forecast storm surges and found that it can obtain better prediction results than the backpropagation (BP) neural network. Liu [4] used long short-term memory (LSTM) to establish a single-station storm surge nowcasting model, and the model using the wind speed and wind direction process data in the previous 2 hours and the tide level process data in the previous 7 hours has the smallest error in terms of predicting the astronomical tide and storm tide level in the next 1 to 3 hours.…”
Section: Introductionmentioning
confidence: 99%